Competitiveness of the legal and tax framework of employee stock options in Latvia - Andersone, Marta (Riga Graduate School of Law, 2020)
As evidenced by prior research, an attractive legal and tax framework to enterprises and employees can have a positive effect on the entrepreneurial activity in a country and consequently - the economy. The necessity of legal and tax frameworks for employee stock options has been recognized by institutions of the European Union, as well as the key stakeholders across the European Union, including Latvia. Nevertheless, the progress in developing satisfactory legal and tax frameworks in Member States has been slow. This paper compares legal and tax framework of employee stock options in Latvia, Estonia and Germany by analysing plan scope, strike prices, bureaucracy, and taxation aspects of employee stock options. The paper concludes that the most important differences in the legal and tax frameworks are found under the plan scope and the availability of tax exemption and that the lack of available tax exemptions to LLCs for using ESOs and the presence of strict rules to qualify for tax exemptions for JSCs negatively impacts the competitiveness of the legal and tax framework of ESOs in Latvia. It is recommended to review the legal and tax framework of employee stock options in Latvia and thereby provide enterprises with an effective financial participation instrument.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Taxation